A clinical case of diffuse odontogenic facial phlegmon - A. S. Varzhapetian; O. O. Kokar (Patologìâ)
The aim of the work is to describe and discuss an unusual clinical case of diffuse facial phlegmon in order to increase the awareness and competence of clinicians who may encounter similar cases.